Aplicação da tecnologia de impressão 3D no tratamento de fratura coronal do côndilo femoral - Mendonça, Celso Júnio Aguiar (2019)
The use of 3D printing technology has been growing exponentially in several areas of medicine including orthopedic surgery. 3D printing technology uses computational resources such as Computer Aided Design (CAD) and Computer Aided Manufacturing (CAM) programs that allow the segmentation and modeling of bones and implants (osteosynthesis materials and prostheses). For this, we use image exams such as computed tomography (CT) that allows the three-dimensional volumetric reconstruction of the object to be studied. In this way it is possible to perform a study the architecture and bone geometry mainly of sites of complex anatomy such as joints, pelvis and spine. In addition, it allows the accomplishment of virtual surgical planning in a CAD environment for programming such as fracture reduction, osteotomy, positioning and choice of the most appropriate type and size of osteosynthesis or prosthesis material. This technology makes it possible to print anatomical models in real scale using thermoplastics that can be used in surgical simulations for operative training and to choose the positioning of the implant material in the most appropriate place following the virtual surgical planning. The objectives of this study were: To evaluate the accuracy of 3D anatomical model printing from CT images, evaluating the acquisition parameters of the images of the exam; To produce, using computer programs in CAD environment, a 3D virtual anatomical model; Produce and analyze the 3D anatomical model printed with the FDM technology of additive manufacture and evaluate the proposed protocol of surgical planning based on the use of virtual and physical anatomical model in a case study of nonunion of the coronal fracture of the femoral condyle. Conclusion: The use of 3D virtual and printed anatomical model using the FDM additive manufacturing technology and ABS as thermoplastic was shown to be effective and useful in planning and performing the surgical treatment of nonunion of the coronal fracture of the femoral condyle.